Monetary Policy in a Small Open Economy Model: A DSGE-VAR Approach for Switzerland - Gregor Bäurle; Tobias Menz (Swiss National Bank, Study Center Gerzensee, 2008)
We study the transmission of monetary shocks and monetary policy with a behavioral model, corrected for potential misspecification using the DSGE-VAR framework elaborated by DelNegro and Schorfheide (2004). In particular, we investigate if the central bank should react to movements in the nominal exchange rate. We contribute to the empirical literature as we use Swiss data, which is very rarely used in that context.
Keywords: C11; C32; E58; 330; Bayesian Analysis; DSGE-VAR; Small Open Economy; Optimal Policy; Geldpolitik; Geldpolitische Transmission; Schock; Prognoseverfahren; Kleine offene Volkswirtschaft; Bayes-Statistik; Dynamisches Gleichgewicht; VAR-Modell; Schätzung; Schweiz